(untitled) (Nigerian Journal of Technology, 2015)
The performance of a cellular network is assessed in terms of key performance indicators (KPI) based on statistics generated from drive tests or network management systems. However, drive tests give the ‘feel’ of the designed network as it is experienced by the subscribers. Therefore, it is used in this study to compare performance of GSM operator networks (W, X, Y and Z) in Minna, Niger State, Nigeria. Transmission Environmental Monitoring System (TEMS) drive test tools were used to collect Log files from the live GSM networks. X network was found to have the best performance from the analysis which was based on target KPIs defined by Nigerian Communications Commission (NCC). All the networks suffered one type of degradation or the other in terms of the KPIs. The research then suggested the required physical optimization measures such as swapping of RF antenna cables, azimuth adjustment and retune of broadcast control channel (BCCH) frequencies in order to resolve the problems identified on W network in this study. http://dx.doi.org/10.4314/njt.v34i2.21